Do tunneling states and boson peak persist or disappear in extremely stabilized glasses? - Ramos, M. A.; Pérez-Castañeda, T.; Jiménez-Riobóo, R. J.; Rodríguez-Tinoco, C.; Rodríguez-Viejo, J. (Хабаршы. Физика сериясы, 2015)
We have investigated how extreme thermal histories in glasses can affect their universal properties at low temperatures. In particular, we have studied two materials which allow us to access highly-stable glassy states, as well as their corresponding conventional glasses, in two different ways: (i) amber [1], the fossilized natural resin, which is a glass which has experienced a hyperaging process for about one hundred million years; and (ii) ultrastable thin-film glasses of indomethacin [2] (an organic molecule commonly used in pharmaceuticals), prepared by physical vapor deposition at temperatures around 85% of its glass-transition temperature.